Proposals for the structure, content and composition of the sectoral standard of inventory of lands of the government institutions and enterprises of the NAAS - Dorosh, Y.; Dorosh, O.; Kharytonenko, R.; Melnyk, D. (Land Management, Cadastre and Land Monitoring, 2020)
Regulatory acts and scientific publications relating to the works on inventory of lands of state institutions and enterprises of the National Academy of Agrarian Sciences of Ukraine (hereinafter – NAAS) have been analyzed. It was revealed that the current legislation and just adopted “Procedure of Inventory of Lands” subject to the Decree of the Cabinet of Ministers of Ukraine No.476 of June 5th, 2019 does not include any norms that would consider the specifics of the land use by scientific organizations; their research fields and valuable lands for conducting scientific research should be taken into account when entering the data in the State Land Cadastre, as well as the property rights to them should be registered. The attention is drawn to the problem of legal uncertainty concerning boundaries of lands of state institutions and enterprises of NAAS. The specific functional peculiarities of agricultural land use by state institutions and enterprises of NAAS are considered. In this regard, the structure, content and composition of the main provisions of the industry standard for land inventory of state institutions and enterprises of the NAAS are proposed, which will become a regulatory tool for the preparation of the technical documentation on land management for the implementation of this type of work, and the information obtained will be the basis for the resolution of mature problems concerning the agricultural lands used by these state institutions and enterprises of NAAS. Key words: standardization, industry standard, land inventory, land use for scientific research.